The impact of using SGLT-2 inhibitor on left ventricular longitudinal strain and NT-proBNP levels during six-month follow-up in diabetic patients with and without coronary artery disease with preserved ejection fraction - Biter, Halil İbrahim; Çakal, Sinem; Çakal, Beytullah; Apaydın, Ziya; Kılınç, Ali Yaşar; Oğuz, Hüseyin; Yıldız, Sinan; Oğur, Hasan; Belen, Erdal; Şimşek, Emel (My University, 2024)
Background: Optimal glycemic control is necessary to prevent cardiovascular events in patients with type 2 diabetes. The positive impact of sodium-glucose cotransporter-2 inhibitors (SGLT2i) on cardiovascular events and mortality in these patients has been demonstrated by previous studies although the mechanism is unclear. Aims: We aimed to compare the influence of SGLT2i on left ventricular remodeling and strain in diabetic patients with coronary artery disease (CAD) and without CAD during 6-month follow-up. Methods: Between October 2021 and June 2022, 100 diabetic patients with preserved ejection fraction (HbA1c levels 6.5-10%) were started on SGLT2i (empagliflozin or dapagliflozin) and were prospectively followed up. Conventional and speckle-tracking echocardiography was performed by blinded sonographers, at baseline and then at 1 month and 6 months of treatment. After 6 months, the initial and biochemical blood tests were administered, and N-terminal pro-B-type natriuretic peptide levels of the patients were measured. Results: Patients with CAD were older (P = 0.008), more frequently hypertensive (P = 0.035), and had dyslipidemia (P = 0.021). N-terminal pro-B-type natriuretic peptide levels did not change significantly after treatment in both groups. Left ventricular ejection fraction, global, 2-chamber, and 3-chamber strain values were improved significantly following SGLTi administration for the overall patient cohort, regardless of CAD status (P <0.05 for all groups). Conclusions: Treatment with SGLT2i resulted in improvement in left ventricular strain parameters, which indicates that they might have a positive impact on outcomes for diabetic patients with preserved EF.
Keywords: Heart Failure; Preserved Ejection Fraction; Strain Echocardiography